2020
DOI: 10.3390/ijerph17176370
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Physical Competence in Overweight and Obese Children: An Intervention Study

Abstract: With the current obesity epidemic and the decline of fitness among school-aged children, the importance of obesity interventions to promote physical activity and healthy habits has become indisputable. The purpose of this study was to assess the efficacy of a school-based multicomponent intervention in increasing physical activity (PA) levels, actual physical abilities, and perceived physical abilities in clinical and nonclinical samples of overweight/obese boys and girls aged 10–12 years. The clinical interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 57 publications
(89 reference statements)
1
22
0
Order By: Relevance
“…In this respect, the school environment is ideal for carrying out preventive health education actions due to its structure, effectiveness and wide coverage of individuals [ 56 ]. In addition, studies have already shown that these interventions can positively influence fruit and vegetable consumption, nutritional knowledge, energy and sugar intake [ 57 ] and physical activity [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, the school environment is ideal for carrying out preventive health education actions due to its structure, effectiveness and wide coverage of individuals [ 56 ]. In addition, studies have already shown that these interventions can positively influence fruit and vegetable consumption, nutritional knowledge, energy and sugar intake [ 57 ] and physical activity [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the school environment is ideal for carrying out preventive health education actions due to its structure, effectiveness and wide coverage of individuals [56]. In addition, studies have already shown that these interventions can positively influence fruit and vegetable consumption, nutritional knowledge, energy and sugar intake [57] and physical activity [26]. Health education activities carried out during the intervention stage increased children's knowledge of eating, nutrition, and physical activity in the post-intervention period (p-value < 0.05).…”
Section: Evaluation Of Pre-and Post-intervention Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since physical inactivity is especially prevalent among university students, interventions designed to mitigate these risk factors are necessary. Interventions and reviews have already demonstrated that the above mentioned risk factors could be significantly reduced through physical activity both in children as in adults (49,50,53,52). In addition to BMI, the physical-activity-based interventions in this systematic review have shown further improvements in risk factors of physical inactivity.…”
Section: Discussionmentioning
confidence: 64%
“…There are already many approaches to increase physical activity and reduce BMI. Positive effects of such interventions have been confirmed on adults and children (47,2,(48)(49)(50)(51)(52)(53). Long-term findings on physical activity were highlighted by Reiner et al (2) in their review, which included overweight and obesity in adolescents and adults: Over five years, weight change was examined concerning physical activity.…”
Section: Discussionmentioning
confidence: 99%